GENETIC RELATEDNESS AMONG MAIZE INBRED LINES BASED ON ISSR MARKERS AND ITS ASSOCIATION WITH HETEROSIS AND HYBRID PERFORMANCE - AL-NAGGAR, AHMED MEDHAT MOHAMED; SOLIMAN, AHMED MONGED; HUSSIEN, MONA HASHEM; IBRAHIM, SHAFIK DARWISH; HASSAN MOHAMED, ELHAM MOHAMED (Innovare Journal of Agricultural Sciences, 2022)
The objectives of the present study were to measure the genetic diversity among eight inbred lines of maize using ISSR markers and the correlation coefficients between genetic diversity and each of heterosis and mean performance of hybrids for grain yield. Ten ISSR primers were used in the detection of polymorphism of the eight inbred lines in a laboratorial experiment. Heterosis and mean performance of grain yield/ha in their F1 diallel crosses were measured in a 2-year field experiment using a randomized complete blocks design with three replications. Based on ISSR markers, the genetic similarity coefficients among the eight maize inbred lines ranged from 0.798 (between L17 and IL53) to 0.943 (between IL80 and IL84) with an average of 0.869. Unique bands associated with maize inbred lines were identified. The results revealed that the genetic diversity among the inbred lines based on ISSR markers showed a significant, and negative relationship with mid-parent heterosis and mean performance of grain yield/ha. Further, intensive investigation of a large set of maize inbred lines from diverse populations using a large number of ISSR primers is required for proper understanding of genetic diversity of maize crop. Findings will be valuable for maize breeder, to practice effective selection of parental inbred lines for obtaining maximum heterosis and high mean grain yield/ha in their hybrids.